The Phenomenon of Mass Culture - Sultanov Atabek; Pirnazarov Nurnazar (Zien Journals, 2021)
In this article, the authors analyze the problems of mass culture, which is a multifunctional, objective phenomenon of the modern stage of culture. Mass culture, in which all strata of the population are involved, has its own laws of origin and development, permeates all types and forms of culture.
Keywords: Mass culture; society; cultural industry; phenomenon